The Function of the Regional People's Representative Council (DPRD) of Gorontalo Regency in Environmental Supervision - Umar, Cindrawati; Tilome, Apris Ara; Akbar, Muh. Firyal (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study examines the function of environmental supervision by the DPRD of Gorontalo Regency with a focus on three main indicators: data and information transparency, coordination with the Environmental Service (DLH), and community involvement. The research method uses a qualitative approach with a descriptive research type. The primary data sources in this study consisted of eight informants, namely DPRD members, DLH representatives, and community leaders. The results of the study indicate that transparent data and information access presented by the DPRD of Gorontalo Regency has not been maximized and open either through social media or other information media that can be accessed directly by the community. Coordination between the DPRD and the Environmental Service of Gorontalo Regency has been well established between the two institutions by conducting RDP (Hearing Meeting) from the Environmental Service followed by programs run by DLH under supervision from the DPRD. For the involvement of the community that plays a role in environmental supervision, it has been formed well in villages/sub-districts but is considered ineffective, thus creating challenges for the DPRD and DLH in handling environmental problems, especially the level of public awareness which is considered still lacking in responding to environmental problems that arise due to the actions of the community itself.